TEACHING TRANSLATION: - Rohmah, Rina Alfikawati; Kamalia, Zida (LPPM Universitas Pancasakti Tegal, 2017)
Google Translate as the recent platform which enables people translate from one language to others has been hype nowadays.On the other hand, inaccurate result in translating frequently happens. In accordance with that, Google Translate lets everyone help them in correcting the result of translation through their Google account. They are asked to fix inaccurate words then give corrections or translate from one language to others. This idea has been brought as teaching method in Translation course for EFL learners at Department of English of Universitas Negeri Malang. By giving contribution in translating the words, they will get badges and stats as rewards and become the lecturer?s assessment. Therefore, the researchers are going to analyze the effectiveness of Google Translate based in Translation course. Meanwhile, the significance of this study is to give insight for education practitioners in developing teaching method of Translation. The data is analyzed using qualitative descriptive by distributing questionnaire to twenty seven EFL learners who took the course and interviewing the lecturer who applied this method.